Exploring the dark-side of fitness trackers: Normalization, objectification and the anaesthetisation of human experience. Issue 2 (August 2018) - Toner, John
Abstract: Fitness trackers or 'wearables' are being used by an ever-increasing number of exercisers to self-monitor their health, wellbeing and fitness. While acknowledging that many users find self-tracking devices to be an important part of their exercise regime, the current paper draws on phenomenological and empirical evidence to argue that the use of fitness trackers for the purposes of "bio-monitoring" may have a number of undesirable consequences. I argue that the prolonged use of these devices may, in some cases, normalize/objectify the embodied subject and contribute to an anesthetisation of human experience. This arises as neo-liberal projects encourage "self-trackers" to consider their bodily functioning in quantifiable terms thereby reducing the attention that one may pay to the embodied sensations that accompany physical activity. I suggest that this is likely to hinder one's enjoyment of exercise and prevent users from generating the flexible and adaptive habits that are necessary to expand one's productive capacities in the world. I conclude by briefly considering how wearable devices may be used in a manner which counteracts the surveillance or regulatory intentions of bio-monitoring technologies and allows users to repurpose these technologies in ways which work for them.